Jane Pfefferkorn playing the alto recorder, 1965. - (:unkn) unknown (Forsyth County Public Library, 2008)
WSJ 5-9-65 p.1C.
Jane Pfefferkorn playing the alto recorder, 1965. She is advertising the membership drive for the Winston-Salem Symphony Guild.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth